Effects of grazing on alpine grassland soil available nutrients across the Tibetan Plateau - Zhou, Tongyong; Yang, Hui; Du, Yangong (Frontiers in Soil Science, 2025)
IntroductionAlpine grasslands on the Tibetan Plateau are increasingly affected by grazing, resulting in complex changes in soil nutrient availability.MethodsThis meta-analysis evaluates the effects of different grazing intensities on soil available nitrogen (AN), phosphorus (AP), and potassium (AK), and identifies key environmental drivers.ResultsResults show that grazing significantly increased AN by 11.9% and reduced AK by 14.5%, while its impact on AP was negligible. Light grazing (LG) and moderate grazing (MG) both significantly enhanced AN, with increases of 6.88% and 17.90%, respectively, whereas heavy grazing (HG) reduced AN by 1.52%. LG and MG also positively affected AP, whereas HG caused a substantial decline of 11.04%. In terms of AK, LG led to a slight increase (2.05%), but MG and HG both caused significant reductions of 11.01% and 10.35%, respectively. Temperature emerged as a critical factor, reducing AN and increasing AK, highlighting its importance under climate change scenarios.DiscussionThese findings emphasize that grazing intensity plays a pivotal role in regulating soil nutrient levels, with LG showing the most consistent positive effects on nutrient availability. Thus, managing grazing intensity, particularly favoring light grazing, is crucial to maintaining soil fertility and supporting the long-term productivity of alpine grasslands on the Tibetan Plateau.